Measuring Access to Higher Education in India - Mittal, Pankaj; Patwardhan, Bhushan (International Higher Education, 2020)
The gross enrollment ratio (GER) is a universally accepted indicator for the level of participation in higher education. India has adopted policies to increase the GER by expanding its higher education capacity and by promoting distance and online modes of delivery. However, the low number of students eligible for admission to higher education is a major limiting factor. The eligible enrollment ratio (EER) is a more realistic indicator.